Containing the COVID-19 pandemic: What determined the speed of government interventions? - Iulia Siedschlag; Weijie Yan (The Economic and Social Research Institute (ESRI), 2020)
This paper examines the speed with which governments introduced lockdown measures to contain the COVID-19 pandemic. We use data on daily confirmed COVID-19 cases and related deaths combined with information on containment measures available for 124 countries as well as a range of annual country-specific data. In terms of methodology, we estimate time-to-event models to analyse the speed of starting government containment measures and the speed with which such measures reached their highest level from the first confirmed COVID-19 case and the first COVID-19 related death. Our results indicate that governments in countries with a weaker health system capacity and in countries with a larger share of elderly populations were more likely to start lockdown measures faster. Smaller and more open economies were more likely to move faster to the highest level of containment measures.
Keywords: I18; H12; J18; 330; COVID-19 pandemic; government lockdown measures; speed of government interventions; health system capacity; time-to-event models